A representação social do conceito de evolução por professores de biologia - Agnoletto, Renata (2011)
The present work results from the research for a dissertation which aimed to describe the social representations of the evolution concept held by a group of Biology teachers. Convinced of the centrality of this subject through the teaching of Science, and of the importance of the naturalist Charles Darwin for the scientific though, we justify our research also by the official documents which regulate the approach of such subject in elementary and high schools. Our questions were: Do teachers understand and teach the evolution concept according to Darwin's concept? Are teachers able to regard the Biology subject by means of an evolutionist perspective and to acknowledge the importance of approaching such theme in different grades? Do they have basic notions on the theory proposed by Darwin, or do they have internalized distortions of it through their lives? With the intent of characterizing these notions about the teachers responsible for the teaching of evolution, we have opted to use the Theory of Social Representations (SR) proposed by Serge Moscovici in the 1960's. This theory considers that, inside the social groups, there is an instituted knowledge that is diffused through the individual's behavior in relation to objects, to the environment and to their peers. By characterizing a social representation, we could infer how the individual behaves in relation to a theme, since the representations relate the whole process of experience and personal signification of one individual and the group in which s/he is inserted in his/her daily life. The surveyed group was composed by 17 Biology teachers in the cities of Maringá and Cascavel, in the State of Paraná, which were invited to participate in it by giving an interview, first recorded and then transcribed, to be submitted to analysis. We believe that during the process of didactic transposition, the teachers have chosen arguments based on their representations of the subject they are teaching and, thus, we have selected the rhetorical analysis proposed by Mazzotti (2008) in order to characterize the social representations held by the group due to the importance of language in the representational process and its centrality in education. As a result, we have obtained the social representation of evolution based in the action of an agent (Nature) with an occult intent of progress, the general idea of an existing gene or something that leads to evolution. Nothing is originated by chance. There is a determined orientation in the speech of the surveyed teachers, in which this agent is either the gene or the natural selection. The teachers' speeches do not go beyond the one found in didactic books, and we have highlighted, as well, the anthropocentric justifications for the study of evolution, which pointed out the subject of Biology as a subsidy to the apprehension of the origin of human life.